An investigation into EFL teachers’ perceptions and practice of teaching phonics to young language learners : - Đỗ, Nguyệt Hồng (Can Tho University, 2015)
This study was conducted to investigate teachers' perceptions and their practice of teaching phonics to young language learners in EFL classroom